REVIEW: OPTIMALISASI PENGURANGAN BAU TENGIK PADA MINYAK KELAPA SAWIT MELALUI PENAMBAHAN TANAMAN OBAT AROMATIK - Simanjuntak, Yohana Decinta; Chairani, Syasmita; Saragih, Sri Wahyuna; Wagino (Institut Teknologi Sawit Indonesia (ITSI), 2024)
Crude Palm Oil is one type of vegetable oil that is extensively utilized in many different industries around the world, one of which is as a basic ingredient for cooking oil products. In Indonesia, Palm oil is among the abundant agricultural commodities. Therefore, palm oil is the right decision to address community needs across a range of domains. Crude palm oil has a high beta-carotene content, an initial compound of vitamin A, which gives the oil a reddish color. The dominant color of red or orange fruits or vegetables is a characteristic of crude palm oil from other types of vegetable oils. This investigation was carried out to examine the impact of adding aromatic medicinal plant extracts on the aroma and taste characteristics of palm oil when high water content increases free fatty acid levels that can cause CPO rancidity. Various experimental methods were used with data obtained from a careful literature review. The final results showed that variations in the addition of these ingredients significantly affected the aroma and taste of palm oil, highlighting the potential for innovation in product development and the food industry with repeated frying processes.